Electrophilic Lipid Mediator 15-Deoxy-Δ(12,14)-Prostaglandin J(2) Modifies Glucocorticoid Signaling via Receptor SUMOylation - Paakinaho, Ville (American Society for Microbiology, 2014)
Cortisol, the central stress hormone in humans, activates the glucocorticoid receptor (GR). Anti-inflammatory effects are the most important pharmaceutical effects mediated by the GR. Inasmuch as electrophilic cyclopentenone prostaglandin 15-deoxy-Δ(12,14)-prostaglandin J(2) (15d-PGJ(2)) has potent anti-inflammatory properties and activates the SUMOylation pathway, we have investigated the effect of 15d-PGJ(2) on glucocorticoid signaling and receptor SUMOylation. To this end, we studied isogenic HEK293 cells expressing either wild-type GR or SUMOylation-defective GR. Interestingly, 15d-PGJ(2) triggered SUMO-2 and -3 (SUMO-2/3) modification in the primary SUMOylation sites of the GR. Gene expression profiling and pathway analyses indicate that 15d-PGJ(2) inhibits GR signaling in a genome-wide fashion that is significantly dependent on the GR SUMOylation sites. Chromatin immunoprecipitation assays showed that the repressive effect of 15d-PGJ(2) on GR target gene expression occurs in parallel with the inhibition of receptor binding to the target gene chromatin. Furthermore, depletion of UBC9, the sole SUMO E2 conjugase, from HEK293 cells confirmed the involvement of active SUMOylation in the regulatory process. Taken together, our data indicate that GR SUMOylation modulates the glucocorticoid signaling during acute cell stress. Our data also suggest that GR SUMOylation modulates cross talk of the glucocorticoid signaling with other transcription factors that are responsive to cell stress.